Radiant Times Series (RTS) For Equatorial Climates - Boniface, Christopher Jantai; Miyanaga, Norifumi; Mohd Danial, Bin Ibrahim (2015)
Air conditioning units are the most significant energy user in a building. Therefore, an accurate cooling load calculation is important to optimize the design of these air conditioning units for a better system for the building energy load. American Society of Heating, Refrigerating and Air Conditioning (ASHRAE) has developed a method called Radiant Times Series (RTS) to improve the accuracy of cooling load calculation. There are several traditional cooling load calculation methods commonly practiced by designers in Malaysia especially Rules of Thumbs, CLTD (Cooling Load Temperature Difference) and TFM (Transfer Function Method). Designer may considered higher safety factor for conventional method because of constraint in initial parameter consideration, thus this will promote higher loading and over designed air conditioning system. This study will discuss the various types of cooling load methods in equatorial climates (hot and humid), where buildings in Malaysia is used as a subject in this paper. The results would be useful for Mechanical, Ventilation and Air Conditioning (MVAC) designer to consider and design a better and optimum system for the building. The finding shows that the huge convocation hall with estimated occupant of 5000 tenants shall be design between the ranges of Cooling Load per Square Feet, of 70 Btu/Hr.ft2 to 125 Btu/Hr.ft2 based on RTS method and CLTD method respectively. Meanwhile, for office building the design shall be between the ranges of Cooling Load per Square Feet, of 33.81 Btu/Hr.ft2 to 46.79 Btu/Hr.ft2 based on RTS method and CLTD method respectively. These values are to be achieved comfort cooling for the respective building. The results also showed that the accuracy of cooling load will be determined by the considered parameter of the cooling load methods. It's important to use this method in Malaysian perspectives because of the accuracy and recommended for other hot and humid countries.